P794 Signs and symptoms associated with single-pathogen nongonococcal urethritis in men. (14th July 2019) - Batteiger, Teresa; Jordan, Stephen; Toh, Evelyn; Williams, James; Fortenberry, Lora; Batteiger, Byron; Nelson, David
Abstract : Background: Syndromic management remains the standard nongonococcal urethritis (NGU) treatment approach. Whether pathogen-specific signs/symptoms inform treatment decisions remains unclear. We identified men with single- and mixed-pathogen NGU and assessed for the presence of pathogen-specific signs or symptoms to improve syndromic management. Methods: As part of an ongoing cohort study (the Idiopathic Urethritis Men's Project [IUMP]), we recruited men with NGU. NGU was diagnosed by signs and/or symptoms of urethritis, and a urethral Gram stain with ≥ 5 neutrophils per high-power field without evidence of gram negative intracellular diplococci. Participants underwent a clinical history and physical exam, which documented specific self-reported symptoms and clinician observed signs. Single- and mixed-infections were identified by NAAT testing of first-catch urine for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), Mycoplasma genitalium (MG), Trichomonas vaginalis (TV), and Ureaplasma urealyticum (UU); five-pathogen-negative cases were classified as idiopathic urethritis (IU). Results: One hundred fifty-five men with NGU are included in this analysis. The median age was 28 (range 18–63), 101 (65%) were African American, and 135 (87%) self-identified as heterosexual. The most commonly reported symptom was urethral discharge (92%), followed by burning/tingling (37%), and dysuria (28%). Over half of these men reported more than one symptom (58%). Single-pathogen NGU was detected in 99 (64%) men, mixed-pathogen in 14 (9%), and IU in 42 (27%). For single pathogen NGU, 53 (34%) had CT, 26 (17%) had MG, 3 (2%) had TV, and 17 (11%) had UU. We compared single-pathogen NGU, mixed-infection and IU for differences in signs or symptoms and found no pathogen-specific differences. Conclusion: In men with NGU, no pathogen-specific signs and symptoms were identified that could inform treatment decisions. Pathogen-specific point-of-care tests are needed. Disclosure: No significant relationships.